Accelerated mononuclear cell telomere attrition in breast cancer survivors with depression history: A 2‐year longitudinal cohort study. Issue 16 (7th June 2022) - Carroll, Judith E.; Olmstead, Richard; Haque, Reina; Irwin, Michael R.
Abstract : Background: Cancer treatments are thought to accelerate biological aging, although this trajectory is highly variable. Depression is more prevalent in breast cancer survivors and is thought to be a vulnerability factor for biological aging. A lifetime history of depression and cumulative lifetime number of depression episodes could hypothetically be associated with an accelerated rate of biological aging as indexed by attrition of telomere length in a prospective cohort of breast cancer survivors who were not currently depressed. Methods: Breast cancer survivors ( n  = 206) without current depression were recruited from a large community‐based health plan and were assessed for depression history by a structured diagnostic interview. Blood specimens were provided at baseline and every 8 months over 24 months to measure peripheral blood mononuclear cell (PBMC) telomere length. Mixed linear models examined associations of depression history and number of depression episodes with change in telomere length, adjusting for demographic, comorbidity, and cancer‐specific factors. Results: In the fully adjusted model, depression history predicted attrition of PBMC telomere length over 24 months (Beta [SE] = −.006 [.002], p  = .001). Greater number of depressive episodes over the lifetime was also associated with accelerated attrition of PBMC telomere length over 24 months (Beta [SE] = −.004 [.001], p  = .001). Conclusions: In breast cancer survivors without current depression, telomere attrition over 24 months was greatest in those with a lifetime depression history, particularly those with the greatest number of episodes of major depressive disorder over their lifetime. Depression history and its cumulative burden may contribute to accelerated biological aging, with implications for risk of morbidity and mortality in breast cancer survivors. Abstract : Peripheral blood mononuclear cell telomere attrition over 24 months was greatest in breast cancer survivors who had a lifetime depression history. Depression history and its cumulative burden may contribute to accelerated biological aging in breast cancer survivors.